Analysis of IEEE 802.11b wireless security for university wireless LAN design - Chan,, FKL; Issac,, B; Hoon, , AH (2005)
Wireless Local Area Network has been very popular nowadays especially in public places like shopping malls, airports, coffee cafes, hotels and in universities. However, many people that implemented the WLAN have not been concerned with the wireless security issues that expose their network to dangerous intruders. This paper aims to explain the analysis of wireless security issues based on IEEE802.11b standard with practical implementation and attacks with security suggestions. The WLAN test bed was implemented at the Swinburne University iSECURES research lab for further planning and design of the University WLAN.